2008
DOI: 10.1007/s10096-008-0589-0
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of common aerobic pathogens to tigecycline: results of a surveillance study in Germany

Abstract: Tigecycline is a novel antimicrobial agent for parenteral use encompassing a broad spectrum of bacterial pathogens, including multi-resistant organisms. Here, we report the results of the first nationwide surveillance trial that was conducted in order to evaluate the susceptibility of bacterial isolates to tigecycline in a European country prior to its clinical use. A total of 2,610 Gram-positive and Gram-negative organisms recovered from hospitalized patients were tested. Minimum inhibitory concentrations (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…The low susceptibility of P. aeruginosa in this non-interventional study is in line with previous results [30,31] confirming that tigecycline does not have reliable in vitro activity against this pathogen. The favourable results on the susceptibility of the other pathogens to tigecycline are consistent with the experience gathered in the German Tigecycline Evaluation Surveillance Trial [14,15]. In this nationwide two-phase multi-centre surveillance study, the susceptibility of bacterial isolates from hospitalized patients with community- or hospital-acquired infections was evaluated before and 1 year after the introduction of tigecycline into clinical use.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The low susceptibility of P. aeruginosa in this non-interventional study is in line with previous results [30,31] confirming that tigecycline does not have reliable in vitro activity against this pathogen. The favourable results on the susceptibility of the other pathogens to tigecycline are consistent with the experience gathered in the German Tigecycline Evaluation Surveillance Trial [14,15]. In this nationwide two-phase multi-centre surveillance study, the susceptibility of bacterial isolates from hospitalized patients with community- or hospital-acquired infections was evaluated before and 1 year after the introduction of tigecycline into clinical use.…”
Section: Discussionsupporting
confidence: 72%
“…Designed to circumvent the common drug resistance mechanisms of efflux and ribosomal protection, tigecycline is active in vitro against antibiotic-resistant bacteria such as VRE (E. faecalis and E. faecium), methicillin-resistant S. aureus, ESBL-producing enteric Gram-negative bacteria, as well as isolates of the A. baumannii group [13,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…There have been two studies reporting that tigecyclineresistant staphylococcus strains were found. In one, among a total of 2610 species (Gram-positive and Gram-negative), one S. haemolyticus was found to be resistant to tigecycline [23]. In the other study, tigecycline resistance was detected in 1.8% of the 1989 community-acquired MRSA strains [27].…”
Section: Discussionmentioning
confidence: 91%
“…Mechanisms of tigecycline resistance, such as the RND efflux system, also provide resistance to tetracyclines. Although tigecycline remains more active than other antimicrobials usually tested against MDR pathogens (e.g., fluoroquinolones and ␀-lactams), several tigecyclineresistant strains have been described in recent years (146).…”
Section: Resistance To Tetracyclines and Tigecycline And Effect On VImentioning
confidence: 99%